Internal exposure levels of polycyclic aromatic hydrocarbons in children and adolescents: a systematic review and meta-analysis - Xin Huang; Xu Deng; Wenyan Li; Shudan Liu; Yiwen Chen; Bo Yang; Qin Liu (Komiyama Printing Co. Ltd, 2019)
Abstract Polycyclic aromatic hydrocarbons (PAHs) are widely found in the environment, and comparing to adults, children are more vulnerable to PAHs exposure. Urinary metabolites of PAHs are used as preferred biomarkers to estimate the PAHs exposure. Systematic review on the internal exposure level of children and adolescents is rare. We aimed to calculate the internal exposure levels of PAHs in children and adolescents and compare the levels of PAHs internal exposure in various children groups. We searched PubMed, OVID, Web of Science, EBSCO, ACS, and four Chinese databases, and all studies examining the urinary concentrations of PAHs in children and adolescent were identified. The total exposure level of 11 PAHs metabolites were pooled. Standard mean difference (SMD) and 95% confidence intervals (CIs) of PAHs urinary concentration were calculated and pooled by RevMan5.3 to compare the exposure levels of different children groups. We found that 1-OHPyr, 2-OHNap, 2-OHFlu, 3-OHPhe, and 4-OHPhe were five PAHs metabolites most commonly studied in existing studies in children, and their total exposure levels were 0.38 ± 0.98, 2.32 ± 4.83, 0.81 ± 1.54, 0.09 ± 0.14, 0.03 ± 0.10 μmol/mol creatinine, respectively. The meta-analysis showed that the levels of 1-OHPyr were higher in higher environmental exposure group (SMD = 0.21, 95% CI = 0.03~0.40), ETS exposure group (SMD = 0.31, 95% CI = 0.08~0.54), and 6~11 years group (SMD = 0.16, 95% CI = 0.09~0.24); the level of 2-OHNap (SMD = 0.27, 95% CI = 0.01~0.53) was higher in higher environmental exposure group; however, the levels of 3-OHPhe (SMD = − 0.34, 95% CI = − 0.57~− 0.12) and 4-OHPhe (SMD = − 0.48, 95% CI = − 0.69~− 0.28) were higher in lower environmental exposure group. The levels of 1-OHPyr (SMD = − 0.01, 95% CI = − 0.11~0.10) and 2-OHNap (SMD = 0.01, 95% CI = − 0.20~0.22) were not statistically different between boys and girls. In conclusions, we found that the internal diversity of PAHs existed in children and adolescents, and the level of 1-OHPyr in children and adolescents was in higher status compared with non-occupational people who do not smoke.